Outcomes of Gluteus Maximus and Tensor Fascia Lata Transfer for Primary Deficiency of the Abductors of the Hip. Issue 6 (November 2017) - Chandrasekaran, Sivashankar; Darwish, Nader; Vemula, S. Pavan; Lodhia, Parth; Suarez-Ahedo, Carlos; Domb, Benjamin G.
Purpose: This study aims to present 3 patients' results after undergoing gluteus maximus and tensor fascia lata (TFL) transfer for chronic abductor tears unable to be repaired primarily. Methods: 3 patients were identified intraoperatively as having an abductor tear unable to be repaired primarily. The anterior 1/3 of the gluteus maximus and the posterior 1/3 of the TFL were mobilised and transferred to the greater trochanter in order to reproduce the normal force vector of the gluteus medius and minimus. Data was prospectively collected for changes in gait, abductor strength, and the following patient reported outcomes (PROs): modified Harris Hip Score (mHHS), Nonarthritic Hip Score (NAHS), Hip Outcome Score-Sports Specific Subscale (HOS-SSS), Hip Outcome Score-Activities of Daily Living (HOS-ADL), visual analogue scale (VAS), and satisfaction. Results: The patients were female, 63-75 years old, with BMIs of 23-28. All patients had follow-up at mean 2.1 years (1.25-2.5) with positive Trendelenburg signs preoperatively; 2 patients normalised postoperatively. For 2 patients, abductor strength improved by 2 grades postoperatively; the other patient maintained grade four. 2 patients' PROs all improved; the other patient's PROs all improved except mHHS. Postoperative VAS scores were 0, 0, 1. 2 patients reported maximum satisfaction. Conclusions: This case series suggests that gluteus maximus and TFL transfer for irreparable abductor deficiency may be effective for pain relief, improving abductor strength, and reconstructing abductor function. Although this is a small series, it is to our knowledge the first report of clinical outcomes of this procedure.